Unraveling the adsorption and diffusion behavior of H and O atoms at Zr(0001) surface doped with a Nb/Sn atom: A first-principles study - Rongjian Pan; Aitao Tang; Jiantao Qin; Qingqing Wang; Lu Wu (Heliyon)
With the formation of a surface oxide or hydride layer of the zirconium alloy, the ductility of the nuclear rod decreases obviously. Thus, it is significant to develop a deeply understanding of this process, which may assist in future corrosion and hydrogen embrittlement resistance design for the zirconium alloy. A special focus of this work is an atomistic insight for unraveling the influence of doped alloying elements Nb/Sn on the early stages of oxide and hydride formation of zirconium alloys. The results show that for the effect of Nb/Sn on the adsorption of H at Zr(0001) surface, the adsorption energy of H on the surface of Zr alloys is tend to decrease with the addition of Nb, but for the addition of Sn, it is not significant. For the effect of Nb/Sn on the adsorption of O at Zr(0001) surface, the adsorption energy of O on the surface of Zr alloys is reduced with the addition of Nb and Sn, and the effect of Nb was more remarkable than that of Sn. In case of the diffusion barrier of H from Zr(0001) surface to the interior of Zr bulk, it is reduced with the addition of Nb in Zr(0001), while the addition of Sn does not change much. For the diffusion barrier of O, both are decreased with the addition of Nb or Sn in Zr(0001).